2017
DOI: 10.1371/journal.pone.0179540
|View full text |Cite
|
Sign up to set email alerts
|

Cholecalciferol decreases inflammation and improves vitamin D regulatory enzymes in lymphocytes in the uremic environment: A randomized controlled pilot trial

Abstract: It has been reported that vitamin D regulates the immune system. However, whether vitamin D repletion modulates inflammatory responses in lymphocytes from dialysis patients is unclear. In the clinical trial, thirty-two (32) dialysis patients with 25 vitamin D ≤ 20ng/mL were randomized to receive either supplementation of cholecalciferol 100,000 UI/week/3 months (16 patients) or placebo (16 patients). In the in vitro study, B and T lymphocytes from 12 healthy volunteers (HV) were incubated with or without uremi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 38 publications
3
24
0
Order By: Relevance
“…In support with our suggestion above, VD 3 in our study resulted in significant alleviations in renal and testicular tissue injuries observed in animals exposed to Pb-only. VD 3 also restored and/or preserved the expression of its cellular endogenous molecules compared with positive controls, suggesting a positive feedback regulation, a common phenomenon previously reported by many studies following treatment with VD 49 51 .…”
Section: Discussionsupporting
confidence: 75%
“…In support with our suggestion above, VD 3 in our study resulted in significant alleviations in renal and testicular tissue injuries observed in animals exposed to Pb-only. VD 3 also restored and/or preserved the expression of its cellular endogenous molecules compared with positive controls, suggesting a positive feedback regulation, a common phenomenon previously reported by many studies following treatment with VD 49 51 .…”
Section: Discussionsupporting
confidence: 75%
“…Cholecalciferol supplementation reduces inflammation and, subsequently, the C-reactive protein level [21,22]. The findings from a randomized placebo-controlled clinical trial showed that cholecalciferol supplementation had an anti-inflammatory effect and it increased the expression of the intracellular vitamin D regulatory enzymes within lymphocytes in a uremic environment [23]. In the present study, the association between vitamin D and mortality persisted, even after the model was adjusted for the C-reactive protein levels.…”
Section: Discussionsupporting
confidence: 43%
“…These data have been confirmed in a recent randomized controlled trial showing increased circulating klotho and total antioxidant capacity after 12 weeks of cholecalciferol treatment compared to the placebo group [95]. Human ex vivo studies indicate that vitamin D exerts anti-inflammatory effects on uremic lymphocytes under renal replacement therapy (RRT) [96]. Meta-analyses demonstrating reduced circulating markers of inflammation in mostly non-CKD subjects on vitamin D supplementation [97,98], further supporting a significant role of vitamin D on the hallmarks of ageing.…”
Section: The Endocrine Phosphate-fgf-23-klotho Axis and Premature Agementioning
confidence: 77%